SISTEM INFORMASI AKUNTANSI BERBASIS DESKTOP PADA WATER PARK DUTAMAS BATAM - Sahara, Sahara; Wahyuni, Wahyuni (Sekolah Tinggi Manajemen Informatika dan Komputer GICI, 2021)
The system used in the Wahana Water Park Batam still uses Ms Excel which often experiences problems including data loss and delays in presenting financial data. For the financial system that is used, manuals by writing in books. With these problems, an information system design is needed that is able to overcome the problems that exist at Wahana Water Park. The purpose of this research is to design an accounting information system from ticket sales and other income that is currently running at Wahana Water Park Dutamas Batam and to implement an accounting information system for Wahana Water Park Dutamas Batam based on the system that has been designed. The system is in the form of Data Flow Diagrams (DFD) and Entity Relationship Diagrams. For data storage, the system uses a database so that it can store large amounts of data and does not require a lot of space. System design with interface. The results of this study are that the accounting information system program that has been created can provide convenience in data processing and can solve existing problems with the existence of an accounting information system program, making it easier to calculate incoming money or income, expenses and other costs. For data storage media has been computerized and stored in a database, thus speeding up the search for data.